2015
DOI: 10.1094/mpmi-02-15-0039-r
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Molecular Dialogue Between Gray Mold (Botrytis cinerea) and Grapevine (Vitis vinifera) Reveals a Clear Shift in Defense Mechanisms During Berry Ripening

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 98 publications
3
84
0
Order By: Relevance
“…The cellular target of BOT remains unknown but the recent work of Rossi et al (2011) on Arabidopsis thaliana suggests that BOT induces the hypersensitive response through the salicylic acid and jasmonic acid signaling pathways, thereby acting as an effector of plant cell death. This biological activity fits with the available transcriptomic data: the BOT gene cluster is up-regulated during infection of different hosts including A. thaliana and Vitis vinifera (Gioti et al, 2006;Kelloniemi et al, 2015). In this study, we confirmed that the oxidative stress which Moreover, a MM in which nitrate was replaced by ammonium (12.5 mM (NH 4 ) 2 SO 4 ) was also used, as well as the RM medium.…”
Section: The Role Of Botrydial and Other Botryanes Remains Enigmaticsupporting
confidence: 85%
See 1 more Smart Citation
“…The cellular target of BOT remains unknown but the recent work of Rossi et al (2011) on Arabidopsis thaliana suggests that BOT induces the hypersensitive response through the salicylic acid and jasmonic acid signaling pathways, thereby acting as an effector of plant cell death. This biological activity fits with the available transcriptomic data: the BOT gene cluster is up-regulated during infection of different hosts including A. thaliana and Vitis vinifera (Gioti et al, 2006;Kelloniemi et al, 2015). In this study, we confirmed that the oxidative stress which Moreover, a MM in which nitrate was replaced by ammonium (12.5 mM (NH 4 ) 2 SO 4 ) was also used, as well as the RM medium.…”
Section: The Role Of Botrydial and Other Botryanes Remains Enigmaticsupporting
confidence: 85%
“…S2). Gene expression during infection of grape berries (Kelloniemi et al, 2015) and in the DBcve1, DBclae1 and DBcyoh1 mutants (Schumacher et al, 2015;Simon et al, 2013) suggests that the Bcbot1-Bcbot7 genes are co-regulated while the surrounding genes have different expression profiles. Finally, orthology analysis (Fig.…”
Section: Bcbot6 Regulates the Bcbot Genesmentioning
confidence: 99%
“…H 2 O 2 ‐mediated oxidative cross‐linking and lignin synthesis to reinforce CWA and halt B. cinerea infection were recently shown in grapevine by Kelloniemi et al . (). In their study, the up‐regulation of lignin‐forming enzymes (GLP3 and EXT) together with the accumulation of H 2 O 2 , at the site of Botrytis penetration, was part of the defence mechanisms used by the veraison berry to arrest the pathogen.…”
Section: Discussionmentioning
confidence: 97%
“…Another study on grapes infected at véraison reported the accumulation of reactive oxygen species (ROS), the activation of the salicylic acid (SA)‐dependent pathway and the induction of stilbene and lignin biosynthesis as defence mechanisms to arrest B. cinerea progression (Kelloniemi et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…In conclusion, the ability to produce ABA among Botrytis species seems to be restricted to B. cinerea and possibly to the other polyphagous species B. pseudocinerea . As ABA plays a multifaceted role in plant immunity (Cao et al ., ), its role in B. cinerea /plant interactions has been investigated by several approaches (Sharon et al ., ; Kelloniemi et al ., ). Interestingly, tomato and Arabidopsis ABA‐deficient mutants are more resistant to B. cinerea (Audenaert et al ., ; Liu et al ., ).…”
Section: Discussionmentioning
confidence: 99%